2007
DOI: 10.5194/angeo-25-2413-2007
|View full text |Cite
|
Sign up to set email alerts
|

Scale sizes of intense auroral electric fields observed by Cluster

Abstract: Abstract. The scale sizes of intense (>0.15 V/m, mapped to the ionosphere), high-altitude (4-7 R E geocentric distance) auroral electric fields (measured by the Cluster EFW instrument) have been determined in a statistical study. Monopolar and bipolar electric fields, and converging and diverging events, are separated. The relations between the scale size, the intensity and the potential variation are investigated.The electric field scale sizes are further compared with the scale sizes and widths of the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Karlsson and Marklund (1996) found that the potential variation across the E-field structure has the same order of magnitude for all events and is independent on the E-field peak scale-size. Johansson et al (2007) get similar results for monopolar events when disregarding those scale-size ranges with very large error bars (not shown in their paper is that the same relation appears when all bipolar and monopolar events are merged into one group). Even for thin field-aligned current sheets connected to discrete arcs an inverse relationship between FAC width and FAC intensity has been found Stasiewicz and Potemra, 1998).…”
Section: Connection To Different Substorm Phasessupporting
confidence: 62%
See 3 more Smart Citations
“…Karlsson and Marklund (1996) found that the potential variation across the E-field structure has the same order of magnitude for all events and is independent on the E-field peak scale-size. Johansson et al (2007) get similar results for monopolar events when disregarding those scale-size ranges with very large error bars (not shown in their paper is that the same relation appears when all bipolar and monopolar events are merged into one group). Even for thin field-aligned current sheets connected to discrete arcs an inverse relationship between FAC width and FAC intensity has been found Stasiewicz and Potemra, 1998).…”
Section: Connection To Different Substorm Phasessupporting
confidence: 62%
“…Thus, Haerendel (2000) concluded that the overall plasma convection will not be enhanced by discrete arcs, only the energy conversion rate. However, observations by Johansson et al (2007) of a preferred occurrence of intense E-field events at density boundaries and their often non-bipolar shape indicate that rapid flows along discrete arcs (and their return currents) lead to a net plasma flux. Due to the high velocities of these flows, the net flux above arcs could play an important role for the total plasma transport from the nightside to the dayside.…”
Section: Possible Connection Between Discrete Arcs and Plasma Convectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, 5 years of the Fast Auroral SnapshoT Explorer (FAST) data have shown that the usual width of an inverted-V varies from 20 to 40 km, which is comparable to the peak value of the typical mesoscale auroral arc width of 10-20 km (Partamies et al, 2008). From Freja and Cluster observations, the scale sizes of auroral electric field structures were reported to be ∼ 1-5 km (Karlsson and Marklund, 1996;Johansson et al, 2007). However, these dimensions are much larger than the dimensions of a typical aurora.…”
Section: Introductionmentioning
confidence: 91%